2016
DOI: 10.3389/fendo.2016.00153
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Study of Alkaloids as α-Glucosidase Inhibitors: Hope for the Discovery of Effective Lead Compounds

Abstract: α-Glucosidase (extinction coefficient 3.2.1.20) is a primary carbohydrate metabolizing enzyme that acts on the 1–4 associated α-glucose residues. The inhibition of α-glucosidase slows down the process of carbohydrate digestion and avoids postprandial hyperglycemia, which is a major cause of chronic diabetes-associated complication. This study was designed to evaluate the binding capacity of isolated alkaloids with targeted receptor. For this purpose, the three-dimensional tertiary structure of the α-glucosidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 31 publications
0
16
0
1
Order By: Relevance
“…Zafar and Khan (2016) recently reported that the alkaloids isolated from some of Campanulaceae and Lobelia species, along with standard acarbose, exert significant anti-glucosidase effects. Strong hydrogen bond binding modes of these inhibitors display four interactions between amino acid side chain and hydrogen bonds (Lys155, Glu304, Arg312, and Asn153) [ 82 ].…”
Section: Polyphenols and Plant Familiesmentioning
confidence: 99%
“…Zafar and Khan (2016) recently reported that the alkaloids isolated from some of Campanulaceae and Lobelia species, along with standard acarbose, exert significant anti-glucosidase effects. Strong hydrogen bond binding modes of these inhibitors display four interactions between amino acid side chain and hydrogen bonds (Lys155, Glu304, Arg312, and Asn153) [ 82 ].…”
Section: Polyphenols and Plant Familiesmentioning
confidence: 99%
“…Glucose control is an effective and long-lasting treatment for type II diabetes mellitus, minimizing both cardio-vascular and nervous system symptoms associated with the disease [30,31]. α-glucosidase inhibitors are usually recommended for diabetic patients to decrease postprandial hyperglycemia caused by the breakdown of starch molecules in the small intestine [32].…”
Section: Discussionmentioning
confidence: 99%
“…It differs from α-glucosidase in that it acts on 1,4-bonds. α-Glucosidase is a catalytic enzyme that converts starch and disaccharides into glucose [30]. The process of carbohydrate digestion is slowed when α-glucosidase is inhibited, which helps to avoid postprandial hyperglycemia, which is a primary cause of chronic diabetes and its consequences [31].…”
Section: Binding Interactions Of Luteolin With the α-Glucosidasementioning
confidence: 99%